Determinants of Poverty in Informal Economy of Nepal: Evidence form the FGT Poverty Index - Adhikari, Dipak Bahadur; Kharel, Suman (Nepal Journal of Multidisciplinary Research, 2025)
Background: Even though poverty has decreased in recent years, it is still challenging in Nepal, the rate of decrease is slower. Informal labor accounts for the bulk of urban livelihoods in the research area, and little is known about their susceptibility to poverty and related risk factors. To fill this gap this study examined the prevalence and major determinants of poverty in urban families at different household income quantiles levels in six metropolises of Nepal. Methods: The determinants of poverty in the informal economy have been measured using the FGT poverty index. Similarly, the stabilized indicator (obtained by dividing per-capita income by the poverty line) has been used to examine the determinants of poverty. The inflation-adjusted poverty line income based on NLSS (2010/11) has been used as a reference. Results: The determinants of urban informal household poverty were total family size, education, and working experience of the respondents. The study found that poverty incidence, gap, and severity were significantly higher in Lalitpur Metropolitan City compared to other five metropolitan cities during the study period. This study identified age, education, household size and experience as essential variables. Among them, the age of the respondents and household size are potential measures to reduce poverty in the urban informal sector. This empirical enquiry has revealed that household size is negatively related to poverty incidence. In contrast, the age of respondents is found to be positively related to poverty incidence. Conclusion: The study provides policy suggestions for supporting informal economic activities and employment in Nepal, beneficial to local, provincial, and federal governments, and applicable to other contexts with similar informal economy and poverty. Novelty: This study investigates at the factors that contribute to poverty in urban informal families. It reveals how substantial an impact poverty levels have on variables like family size, education, and employment experience. Household size and respondents age are important factors that impact the incidence of poverty.